Technical and Analytical Approach for Breast Reconstruction With IMAP Propeller Flap - Antonio Spaggiari, MD; Wayne A. Morrison, MD; Caterina Marra, MD; Irene Laura Lusetti, MD; Federica Fiocchi, MD; Massimo Pinelli, MD; Giorgio De Santis, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. The breast-sharing technique uses the lower quadrants discarded from a contralateral symmetrizing reduction mammoplasty to reconstruct the breast after mastectomy. The aim of our study was to revisit this old technique and to improve its vascular predictability by preoperative computed tomography angiography (angio-CT) and intraoperative indocyanine green (ICG) imaging. Methods:. Twenty-six patients were enrolled and assessed by a preoperative angio-CT to localize and evaluate the internal mammary artery perforator (IMAP). In the selected patients, a Wise skin-pattern reduction was designed to allow elevation of a transversely oriented flap including both inferior poles. The flap was based medially on the IMAP. After elevation, evaluation of its arterial and venous perfusion was assessed with ICG. Results:. Eight patients were excluded after pre- and intraoperative studies. Sixteen breast-sharing flaps were performed. A distal flap venous compromise appeared in 2 cases, requiring debridement and flap repositioning, and an infection occurred in 1 case. Four patients had detectable firm lumps that resolved. There were no issues with donor site healing, and a repositioning of the areola was necessary in 2 patients. Conclusions:. Breast-sharing techniques have not gained popularity for many reasons. By combining current understanding of breast cancer behavior, experience with perforator anatomy, and angio-CT and ICG, we believe this study gives a second life to this flap, identifying its weaknesses and improving them. The IMAP propeller flap, simpler and safer in the presence of comorbidities than a free flap, can be a good choice for well-selected candidates.